Dietary Aronia melanocarpa Pomace Supplementation Enhances the Expression of ZO-1 and Occludin and Promotes Intestinal Development in Pigs - Zhongshuai Ren; Hengtong Fang; Jing Zhang; Rui Wang; Wenyu Xiao; Kexin Zheng; Hao Yu; Yun Zhao (Frontiers in Veterinary Science, 2022)
A fruit juice production byproduct, Aronia melanocarpa pomace (AMP) is rich in natural polyphenol antioxidant components. The objectives of this study were to study the effects of dietary AMP supplementation on the feeding outcome and intestinal barrier function of pigs. In total, 27 growing pigs (Duroc × Landrace × Yorkshire, ~60 days, average weight of 27.77 ± 2.87 kg, males and females included at random) were randomly allotted to 3 treatment groups, with 3 repetitions per group and 3 pigs per repetition. At the experiment completion, 2 pigs (close to the average body weight of all experimental pigs) per replicate were slaughtered. The control group (CON group) was fed a basic diet, and the experimental groups were fed 4% (4% AMP group) and 8% (8% AMP group) AMP in the basic diet. These pigs were prefed for 3 days, and the formal experiments were performed for 7 weeks. The results showed that compared with the CON diet, the 4% AMP supplementation significantly increased the average daily gain of pigs (P < 0.05). Regarding intestinal development, 4% AMP significantly increased the jejunal villus height/crypt depth ratio (P < 0.05), and different AMP levels had no significant effect on the pig cecum morphology. Different AMP levels significantly decreased the relative abundance of Proteobacteria (P < 0.05). Regarding other microbial genera, 4% AMP supplementation significantly increased the levels of Lachnospira, Solobacterium, Romboutsia and other beneficial microorganisms (P < 0.05). Different AMP levels significantly decreased the relative abundances of the opportunistic pathogens Escherichia-Shigella and Pseudoscardovia (P < 0.05) and increased the contents of acetic acid and butyric acid in the pig cecal contents (P < 0.05). Compared with the CON treatment, 4% AMP supplementation significantly downregulated the jejunal gene expression of porcine proinflammatory factors (IL-1β, IL-6, IL-8 and TNF-α) and significantly upregulated the jejunal gene expression of ZO-1, Occludin and Claudin-1 (P < 0.05). In conclusion, 4% AMP supplementation in feed is beneficial to overall pig health and growth.